(untitled) (Academia Science Repository, 2023)
Currently, digital technologies in agricultural production play a key role in countries. The world is being increasingly connected as a result of digital technology. Today, the concept of agribusiness is rising to a new level in Uzbekistan. This, in turn, indicates the introduction of investments into the industry and the growth of competition among manufacturers. Therefore, digitization is important to achieve high quality, efficiency, and transparency in the process from choosing a place for the product to be planted in the ground to its cultivation and delivery to consumers. Therefore, this article, dedicated to the study of Uzbek and foreign experience of digitalization in agroindustrial enterprises, is relevant. The article analyzes and studies statistical data about digital technologies used in the agro-industry in several countries, as well as in Uzbekistan.